Husband's Support Associated with Postpartum Family Planning Use - Ratna Dwi Jayanti; Sofiah Rambu Ana Hida; Budi Prasetyo (STIKes Patria Husada Blitar, 2024)
Postpartum contraception prevents about 30% of maternal deaths and 10% of infant deaths within two years. As many as 62% of women who gave birth did not use contraception immediately after delivery. Therefore, this study aimed to analyze the correlation between maternal knowledge and husband's support for postpartum family planning use. This study was a cross-sectional study. The data was collected by interview and filling out questionnaires. The sample included mothers with no history of chronic and infectious diseases who were 42 days postpartum. Bivariate analysis was performed using chi-squared to evaluate the correlation between independent variables and dependent variables. A total of 42 women who gave birth were identified in this study, 21.4% were using postpartum family planning and 78.6% were not using postpartum family planning. Factors associated with postpartum family planning use were husband's support (p=0.038), while maternal knowledge was not associated with postpartum family planning use (p=0.480). Husband's support is associated with postpartum family planning use. Husband's support for family planning will have a significant impact on the family's decision to use a particular family planning tool or method.